Bramwell's helicopter dynamics - Bramwell, A. R. S.; Done, George Taylor Sutton; Balmford, David; Bramwell, A. R. S. (Reston, VA : American Institute of Aeronautics and Astronautics ; Jordan Hill, Oxford, UK : Butterworth-Heinemann, 2001)
Since the original publication of 'Bramwell's Helicopter Dynamics' in 1976, this book has become the definitive text on helicopter dynamics and a fundamental part of the study of the behaviour of helicopters. This new edition builds on the strengths of the original and hence the approach of the first edition is retained. The authors provide a comprehensive overview of helicopter aerodynamics, stability, control, structural dynamics, vibration, aeroelastic and aeromechanical stability. As such, Bramwell's Helicopter Dynamics is essential for all those in aeronautical engineering. THE single volume comprehensive guide for anyone working with helicopters Written by leading worldwide experts in the field
Basic mechanics of rotor systems and helicopter flight -- Rotor aerodynamics in axial flight -- Rotor aerodynamics and dynamics in forward flight -- Trim and performance in axial and forward flight -- Flight dynamics and control -- Rotor aerodynamics in forward flight -- Structural dynamics of elastic blades -- Rotor induced vibration -- Aeroelastic and aeromechanical behaviour.
Rev. ed. of: Helicopter dynamics. c1976.
Includes bibliographical references and index.
Keywords: Helicopters -- Aerodynamics; Rotors -- Dynamics; Electronic books